2004
DOI: 10.21225/d5sp4n
|View full text |Cite
|
Sign up to set email alerts
|

China as a Contesting Ground for Ideologies: Examining the Social and Ideological Forces that Influence China’s Educational System

Abstract: From 1919 to 1921, John Dewey travelled and lectured in China. He received a thunderous welcome and exercised a tremendous influence in China, however, very little has been written about it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…La eficacia del pragmatismo de Deng en el sistema educativo chino se debate en el número del Canadian Journal of University Continuing Education de 2004, lo que sugiere que el enfoque de esta ideología se centra en alcanzar la modernización a través de la ciencia, la tecnología y el conocimiento (mejorando el nivel educativo de la sociedad; Guo, 2004). También se ha sugerido que esta teoría se centra principalmente en la brecha menguante entre China y otras economías en desarrollo (Johnston, 2013).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…La eficacia del pragmatismo de Deng en el sistema educativo chino se debate en el número del Canadian Journal of University Continuing Education de 2004, lo que sugiere que el enfoque de esta ideología se centra en alcanzar la modernización a través de la ciencia, la tecnología y el conocimiento (mejorando el nivel educativo de la sociedad; Guo, 2004). También se ha sugerido que esta teoría se centra principalmente en la brecha menguante entre China y otras economías en desarrollo (Johnston, 2013).…”
Section: Discussionunclassified
“…The effectiveness of Deng’s pragmatism in China’s education system is discussed in a 2004 issue of Canadian Journal of University Continuing Education , which suggests this ideology’s focus on achieving modernization goals through science, technology and knowledge (by improving the educational level in the society; Guo, 2004). It has also been suggested that this theory primarily focuses on narrowing the gap between China and other developing economies (Johnston, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations